Optimization of the performance of the SnTe uni-leg thermoelectric module via metallized layers. (February 2019) - Wang, Xue; Wang, Hongchao; Su, Wenbin; Zhai, Jinze; Wang, Teng; Chen, Tingting; Mehmood, Fahad; Wang, Chunlei
Abstract: We attempt to develop an optimized metallized layer and evaluate the performance for a SnTe uni-leg thermoelectric module by finite-element simulation. The maximum conversion efficiencies of 3.0% and 0.7% have been achieved under ideal and rough contacted thermoelectric modules at ΔT = 600 K. The Ag metal is found to be the optimized metallized layer. The module with metallized Ag layer shows the lowest contact resistance and the best performance. The efficiency reaches about 60% of ideal contacted module. Following that, the pressure forced on module and the surface roughness between the electrode, metallized layer and thermoelectric material have been simulated. With the increase of surface roughness slope, the contact and inner resistances of the thermoelectric module are decreased, and the voltage, maximum output power and efficiency are increased. When the average surface roughness slope is over 0.8, the efficiency reaches 90% of the ideal contacted module. The contact and inner resistances obviously decrease with increasing pressure, while the voltage, maximum output power and efficiency are enhanced. The greater than 90% efficiency of an ideal contacted module is achieved when the pressure is beyond 100 kPa. These simulated results will be beneficial for the fabrication of SnTe-based thermoelectric modules. Highlights: The SnTe uni-leg thermoelectric module are designed and studied. Highest efficiencies of 3%, 0.7% are found for ideal and rough contacted modules. Ag metal is the optimized metallized layer for SnTe uni-leg thermoelectric module. Optimized roughness slope and pressure lead to 90% of maximum of ideal efficiency.